2017
DOI: 10.1101/200451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cancer pharmacogenomic screen powering crowd-sourced advancement of drug combination prediction

Abstract: In the last decade advances in genomics, uptake of targeted therapies, and the advent of personalized treatments have fueled a dramatic change in cancer care. However, the effectiveness of most targeted therapies is short lived, as tumors evolve and develop resistance. Combinations of drugs offer the potential to overcome resistance. The space of possible combinations is vast, and significant advances are required to effectively find optimal treatment regimens tailored to a patient's tumor. DREAM and AstraZene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…While previous research has indicated that synergy is context-specific (Held et al, 2013;Holbeck et al, 2017) , our finding that monotherapy correlation is associated with EOB in the independent DREAM dataset suggest that these mechanisms may constitute general features of synergy ( Figure 7A). Machine learning methods on cell line characteristics and drug combination features can also be effective in predicting synergy (Menden et al, 2018) . However to our knowledge, only the DREAM dataset we used has matched post-treatment expression and viability data, limiting our ability to validate our findings regarding the gene expression patterns associated with synergy in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has indicated that synergy is context-specific (Held et al, 2013;Holbeck et al, 2017) , our finding that monotherapy correlation is associated with EOB in the independent DREAM dataset suggest that these mechanisms may constitute general features of synergy ( Figure 7A). Machine learning methods on cell line characteristics and drug combination features can also be effective in predicting synergy (Menden et al, 2018) . However to our knowledge, only the DREAM dataset we used has matched post-treatment expression and viability data, limiting our ability to validate our findings regarding the gene expression patterns associated with synergy in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The average synergy is computed for each target pair, as the mean of the top three synergistic drug-cell line pairs. We chose a threshold of 20 as synergistic effect, and a score lower than -20 as antagonistic effect, as in Menden et al (10).…”
Section: Fig 2: Influence Of the Similarity Between Target Proteins mentioning
confidence: 99%
“…However, gene mutation information, arguably the most actionable information in the clinic, was not used. In the recent Dialogue on Reverse-Engineering Assessment and Methods (DREAM) drug combination challenge (10), the best performing team used a protein-protein interaction network to augment the genomic features based on their network distance from drug targets. Whilst the best performer achieved outstanding predictability comparable to the level of experimental replicates, synergy was predicted based on supervised machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…We next examined the drug pairs as combination therapies in cell lines 25 and patientderived tumor xenograft models (PDXs) 26 to investigate whether the drug pairs with divergent response and subpopulations with preferential sensitivity to one drug would be associated with efficacy of their combination treatment ( Figure 3C). SEABED first compared the single drug responses of BRAF, MEK and PI3K inhibitors as before to identify BRAF mutant subpopulations with differential response.…”
Section: Subpopulations Of Differential Response Identifies Drug Combmentioning
confidence: 99%
“…The discovery pharmacology dataset was extracted from the The Genomics of Drug Sensitivity in Cancer (GDSC) database 3,4 , while leads from the analysis were validated with the Cancer Cell Line Encyclopedia (CCLE) 5 and the Cancer Therapeutics Response Portal (CTRP) [6][7][8] . Furthermore, suggested drug combinations were validated with cell line responses from the AstraZeneca-DREAM challenge dataset 25 and patient derived xenograft (PDX) models from Gao et al 26 .…”
Section: Pharmacology Datamentioning
confidence: 99%